2021
DOI: 10.1140/epjc/s10052-020-08801-2
|View full text |Cite
|
Sign up to set email alerts
|

SiPM-matrix readout of two-phase argon detectors using electroluminescence in the visible and near infrared range

Abstract: Proportional electroluminescence (EL) in noble gases is used in two-phase detectors for dark matter searches to record (in the gas phase) the ionization signal induced by particle scattering in the liquid phase. The “standard” EL mechanism is considered to be due to noble gas excimer emission in the vacuum ultraviolet (VUV). In addition, there are two alternative mechanisms, producing light in the visible and near infrared (NIR) ranges. The first is due to bremsstrahlung of electrons scattered on neutral atoms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Optical readout of dual-phase LArTPCs offers an alternative approach to the existing and previously described charge readout methodology. As noted previously in Section 3, Townsend multiplication occurring in the THGEM/LEM holes not only produces additional electrons, but also secondary scintillation light (hereafter denoted by "S2"), and studies have shown that-depending on the exact amplification field across the THGEM/LEMmany hundreds of S2 photons can be produced for every drift electron [85][86][87][88][89]. Optical readout therefore relates to the detection of these S2 photons.…”
Section: Optical Readout and The Ariadne Programmentioning
confidence: 94%
See 1 more Smart Citation
“…Optical readout of dual-phase LArTPCs offers an alternative approach to the existing and previously described charge readout methodology. As noted previously in Section 3, Townsend multiplication occurring in the THGEM/LEM holes not only produces additional electrons, but also secondary scintillation light (hereafter denoted by "S2"), and studies have shown that-depending on the exact amplification field across the THGEM/LEMmany hundreds of S2 photons can be produced for every drift electron [85][86][87][88][89]. Optical readout therefore relates to the detection of these S2 photons.…”
Section: Optical Readout and The Ariadne Programmentioning
confidence: 94%
“…Although there are a wide variety of photo-sensitive detectors available with which to observe the S2 light, one of the key requirements for use in a neutrino detector must be the capability for high resolution tracking and position reconstruction, as previously noted in Section 3. With this in mind, in recent years devices such as commercial SiPMs [85,89] and CCDs ("charge-coupled devices") [90] have been used to optically read out smallscale dual-phase LArTPCs, and linearly graded SiPMs ("LG-SiPMs") have also shown potential following initial tests conducted in a gaseous TPC [91]. (LG-SiPMs are a relatively new type of SiPM that natively produces 3D position information using a combination of 2D microcell sensor structure and nanosecond timing resolution [92].)…”
Section: Optical Readout and The Ariadne Programmentioning
confidence: 99%
“…4 Photon emission spectra in gaseous Ar due to excimer scintillations in the VUV measured in [15], NBrS EL at 8.3 Td theoretically calculated in [4] and atomic scintillations in the NIR measured in [16,17]. Also shown is the photon detection efficiency (PDE) of the typical SiPM [18] It has a line emission spectrum [3,16] (see Fig. 4) and a ∼1 Td higher electric field threshold compared to excimer EL, i.e.…”
Section: Overview Of Electroluminescence (El) Mechanisms In Noble Gasesmentioning
confidence: 94%
“…The ReD TPC shares several key characteristics of the future DarkSide-20k experiment, including some elements of the mechanical design, but on a smaller scale. The main technological advance is a readout system based entirely on SiPMs, which offer the possibility of a higher photon detection efficiency relative to typical cryogenic photomultipliers [4,12,13]. The ReD detector discussed here is the first double-phase argon TPC read out by SiPMs to be stably operated on the time scale of months and fully characterised with neutron and γ sources.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 13. Measured S1 distribution from a 83m Kr calibration run with E d = 183 V/cm, superimposed with the normalised environmental background and the best fit to a template (Monte Carlo signal + background data) that accounts for detector resolution.…”
mentioning
confidence: 99%